COMPARING USBILITY SATISFACTION OF GOOGLE MEET AND ZOOM MEETING APPLICATION: CUSTOMER SATISFACTION INDEX AND GAP ANALYSIS CASE STUDY AT K UNIVERSITY - Noni Oktiana Setiowati; Sigit Rahmat Rizalmi; Muhamad Imron Zamzani; Sena Sukmananda Suprapto (Journal of Industrial Engineering Management, 2022)
With the policy of learning from home, the role of information technology become more important. The use of technology in online learning can provide new learning experiences for students. There are several online learning application platforms available and the most popular platforms are Zoom Meeting application and Google Meet. In using the online learning platform, usability aspect is one the most important things. Usability is a measure of the quality of the user experience when interacting with the user-operated device application with the perceived expectations. The purpose of this study is to compare usability satisfaction of Google Meet and Zoom Meeting application using Customer Satisfaction Index (CSI) and GAP analysis. The Customer Satisfaction Index is measured from the five usability aspects of learnability, efficiency, memorability, errors, and satisfaction. Meanwhile, the GAP Analysis is measured based on the perception and expectations of the user of Google Meet and Zoom Meeting application. The result shows that Google Meet has a higher level of usability satisfaction compared to Zoom Meeting application. Google Meet has a usability satisfaction level of 84.29%, meanwhile Zoom Meeting has a usability satisfaction level of 76.67%. The results of GAP analysis on both platforms show that the users made a lot of errors when using Google Meet and find it difficult when using Zoom Meeting application for the first time.